PENDEKATAN SISTEM DALAM PERENCANAAN DAN MANAJEMEN PENDIDIKAN - Abdul Azis Rambe (Ta'dib, 2011)
Planning which are important and strategic functions in education should be carried out by means of system approach. Educational management system approach is elaborated in comprehensive system approach and input-output approach. System approach, according to its goals, is oriented toward the use of various appropriate concepts of system theory. System approach also employs scientific method in solving problems and has orientation toward the use system theory application in managing organizational system.Kata kunci: pendekatan sistem, perencanaan, manajemen pendidikan